(Invited) GaN-Based Multiple 2DEG Channel BRIDGE (Buried Dual Gate) HEMT Technology for High Power and Linearity. (3rd July 2019) - Shinohara, Keisuke; King, Casey; Regan, Eric; Gomez, M P; Bergman, Joshua; Carter, Andrew; Arias, Andrea; Urteaga, Miguel; Brar, Berinder; Page, Ryan; Chaudhuri, Reet; Islam, Moudud; et al.
Abstract : We report on a GaN-based field effect transistor with laterally-gated multiple 2DEG channels, called BRIDGE (buried dual gate) HEMT. Unique operation principle of the transistor enables unprecedented device characteristics suitable for efficient and linear millimeter-wave power amplifier applications. The lateral gate simultaneously modulate multiple 2DEG channels formed in an Al(Ga)N/GaN hetero-structure. A higher electron saturation velocity measured for a lower 2DEG density suggests that the multiple 2DEG channel structure is ideal for obtaining a high current density, and simultaneously enhancing high frequency performance of the transistor. The BRIDGE HEMTs built on a 16-channel HEMT epitaxial structure with a net 2DEG density of 3.3×10 13 cm -2 exhibited a record high knee current density of 3.7 A/mm. The absence of the top contact gate results in negligible current collapse by eliminating a high electric field region at the drain end of the gate – another key feature of the BRIDGE HEMT.